Good Governance: Financial Management of Central and Regional Government - Engkus; Annisa Silvi Elviana; Fadila Amalia; Jun Roynaldi Sunandang; Tira Rahmawati Putri Tawainella (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
In efforts to increase financial transparency and accountability, central and regional governments have a crucial role to play. Transparency and accountability are important principles in conducting good governance as they can both increase public confidence as well as the efficiency and efficiency of budget use. This research uses qualitative methods that are descriptive in nature, one of which is the study of literature or library research so that this research is obtained from relevant books and sources. The aim of this study is to know the transparency and accountability of the financial governance system of the central government and the region in Indonesia and efforts to improve the transparentness and responsibility of financial management of central and regional governments. The results of this research show that in improving transparency of public information, there is a need to monitor the activities of the government, transparency regional budget, socialization of service programmes, and cooperation with the CPC. Transparency and accounting can be said well and in accordance with the expectations of the public if they can implement such improvement efforts. It is therefore hoped that the local and central governments will be able to carry out such work in order to establish a good financial governance system.